JKN Mobile Application as a Governmental Branding for BPJS Kesehatan Indonesia: Evidences from User Experiences - Merlyn Indria Sari; Maya Puspitasari; Muhammad Aufarel Oktariansyah; Mutiara Ayu Shabrina; Shabira Arsa Ghalda; Oan Dania Pasaribu (Jobmark: Journal of Branding and Marketing Communication, 2025)
This study examines the use of the Mobile JKN app, a digital service managed by BPJS Kesehatan Indonesia, to facilitate public healthcare access. The primary focus is on user experience, especially the challenges adults and older people face in operating this application. Using the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) approaches, this study explored factors such as perceived ease of use, benefits, and technical barriers that influence users' adoption of technology from the perspective of Governmental Branding Theory, especially behavioural dimensions.. This research uses a case study method with an explanatory approach. With data collected through in-depth interviews with Mobile JKN users in Jakarta. These interviews delve deeper into the user experience, their perceptions of the application interface, and how this influences their behavior in accessing health services through the application. Data analysis was done using thematic analysis techniques to identify the main themes that emerged from the interviews. Researchers made textual observations from interviews with eight respondents who had downloaded the JKN mobile application. The researcher used aural documentation, which was carried out both through the researcher's hearing and audio recording of the eight respondents who were mobile JKN users. It was found that unfamiliar interfaces, complex application layouts, and frequent technical glitches were major obstacles for users that negatively impacted their perceptions and usage experience. Some app features, such as queue registration and participant data changes, were recognized as helpful in the health administration process. However, most informants felt that the app did not fully meet their needs due to limited functionality and difficulty using it. This study shows that while the JKN Mobile app has the potential to ease access to healthcare through features such as queue registration and participant data management, many users, particularly adults and older people, experience difficulties in operating it. The main obstacles lie in the less intuitive interface, the app layout's complexity, and frequent technical glitches. These factors negatively impacted the app's perceived ease and usefulness, affecting user adoption and satisfaction with this digital service.